2020
DOI: 10.1111/nph.16641
|View full text |Cite
|
Sign up to set email alerts
|

Moderate phosphorus additions consistently affect community composition of arbuscular mycorrhizal fungi in tropical montane forests in southern Ecuador

Abstract: Anthropogenic atmospheric deposition can increase nutrient supply in the most remote ecosystems, potentially affecting soil biodiversity. Arbuscular mycorrhizal fungal (AMF) communities rapidly respond to simulated soil eutrophication in tropical forests. Yet the limited spatio-temporal extent of such manipulations, together with the often unrealistically high fertilization rates employed, impedes generalization of such responses. We sequenced mixed root AMF communities within a seven year-long fully factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 123 publications
(137 reference statements)
6
19
2
Order By: Relevance
“…In our study, N fertilizer did not significantly changed AMF diversity in the wheat rhizosphere, consistent with previous reports (Mueller and Bohannan, 2015;Dueñas et al, 2020). This may reflect the influence of interaction between fertilization and plant on rhizosphere AMF, as the relocation of C to AMF increased with N fertilization.…”
Section: Long-term Nutrient Addition Effects On Rhizosphere Amf Specisupporting
confidence: 92%
See 4 more Smart Citations
“…In our study, N fertilizer did not significantly changed AMF diversity in the wheat rhizosphere, consistent with previous reports (Mueller and Bohannan, 2015;Dueñas et al, 2020). This may reflect the influence of interaction between fertilization and plant on rhizosphere AMF, as the relocation of C to AMF increased with N fertilization.…”
Section: Long-term Nutrient Addition Effects On Rhizosphere Amf Specisupporting
confidence: 92%
“…The NMDS analysis demonstrated that AMF communities differed significantly among different fertilization regimes, suggesting that different N and P additions induced a shift in AMF community composition. These results agree with former findings that the abundance of soil nutrients plays a crucial role in shaping the rhizosphere AMF community (Qin et al, 2015;Dueñas et al, 2020). It was reported that nutrients accumulation caused markedly changes in soil chemical properties, species that are insensitive to the disturbances or efficient in acquiring plant C will increase in relative abundance (Koch et al, 2017;Wang et al, 2018).…”
Section: Long-term Nutrient Addition Changed Rhizosphere Amf Communitsupporting
confidence: 92%
See 3 more Smart Citations